Development of Information Systems Management of Pharmaceutical Preparations and Web-Based Medical Materials at Puskesmas, Medan City - E, Novriani; U, Harahap; W, Wiryanto (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: To determine the effect of web-based information systems on the management of pharmaceutical preparations and BMHP in Medan City Health Center. Methods: This research is a descriptive study with comparative study data collection to see the effect of the SIFAMAS application (System Information Puskesmas) which is designed based on indicators of drug management before and after the application. The design of SIFAMAS as a web-based information system based on the waterfall model and evaluated using alpha and beta tests. This research was conducted in February-July 2020. Results: Before using SIFAMAS, all Puskesmas had not met the standard for accuracy of the number of expired drugs according to the standard, only Puskesmas Mandala, Puskesmas that sent LPLPO on time in February, March, and April respectively 100%; 0%; and 16.67%, and all Puskesmas have not matched the conformity standard for real goods with stock cards. After using SIFAMAS, all Puskesmas did not have expired drugs (0%), delivery of LPLPO was on time (100%), and met the conformity standard for real goods with stock cards (100%). Alpha and beta test results show that SIFAMAS is acceptable and very feasible as a pharmaceutical preparation management information system. Conclusion: SIFAMAS has a good effect and can solve problems related to the management of pharmaceutical preparations in Puskesmas.